2007
DOI: 10.7202/014750ar
|View full text |Cite
|
Sign up to set email alerts
|

Relative Sea-Level Change in the Northern Strait of Georgia, British Columbia*

Abstract: Twenty-four new radiocarbon dates from isolation basin cores, excavations and natural exposures, and an archeological site, constrain relative sea-level change since the last glaciation in the northern Strait of Georgia, British Columbia. Relative sea level fell rapidly from about 150 m elevation to 45 m elevation from 11 750 to 11 000 BP (13 750 to 13 000 cal BP), then its rate of fall slowed. The initial rapid emergence began soon after the transition from proximal to distal glaciomarine sedimentation, when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 32 publications
4
24
0
Order By: Relevance
“…Further north on Quadra and Cortes islands in the northern Strait of Georgia, RSL dropped from above þ146 m amsl after 13.8 ka BP to þ46 m amsl by 13.4 to 12.9 ka BP (James et al, 2005). A low stand in the northern Strait of Georgia has not been identified, although James et al (2005James et al ( , 2009a suggested that a low stand a few meters below present was probably reached prior to 10 ka BP. They argue that after 5 ka BP, RSL rose to, or slightly below þ1.5 m amsl by 2 ka BP.…”
Section: Northern Cascadiamentioning
confidence: 94%
See 1 more Smart Citation
“…Further north on Quadra and Cortes islands in the northern Strait of Georgia, RSL dropped from above þ146 m amsl after 13.8 ka BP to þ46 m amsl by 13.4 to 12.9 ka BP (James et al, 2005). A low stand in the northern Strait of Georgia has not been identified, although James et al (2005James et al ( , 2009a suggested that a low stand a few meters below present was probably reached prior to 10 ka BP. They argue that after 5 ka BP, RSL rose to, or slightly below þ1.5 m amsl by 2 ka BP.…”
Section: Northern Cascadiamentioning
confidence: 94%
“…From 2 ka BP to the present, RSL dropped to its present level (Fig. 6) (James et al, 2005). Further still at Port McNeill on northeast Vancouver Island, marine shells at þ53 m amsl record a high stand around 13.9 to 12.9 ka BP (Howes, 1983) (Fig.…”
Section: Northern Cascadiamentioning
confidence: 97%
“…Corner et al, 2001;Long et al, 2003;Bentley et al, 2005;James et al, 2005;Sparrenbom et al, 2006aSparrenbom et al, , 2006b). This approach is even viewed by some authors as the preferred method for obtaining high-resolution information on sea-level changes (Hutchinson et al, 2004a).…”
Section: Uncertainty In Dating the Lacustrine/marine Transition In Lamentioning
confidence: 97%
“…Deglacial RSL histories of the Pacific coast [75][76][77][78][79][80][81][82][83][84][85] are supplemented by studies of the earthquake and tsunami history of the Cascadia subduction zone along the coasts of British Columbia, Washington, Oregon, and northern California [86][87][88][89][90][91][92][93].…”
Section: Pacific Coastmentioning
confidence: 99%